GAMBARAN PENEMUAN KASUS TUBERKULOSIS PARU OLEH PETUGAS PUSKESMAS DI KABUPATEN SUKOHARJO - Wana Wandhana P.; Martini Martini; Mateus Sakundarno Adi; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Case detection is an important component of tuberculosis control programmes. It helps identify sources of infection, treat them, and thus break the chain of infection. In 2016, CDR of Sukoharjo was under national target while CNR was under the achievements of Central Java. The purpose of this study was to know the characteristics and practices of health workers pulmonary tuberculosis cases finding at Sukoharjo District. This study was descriptive research with a cross sectional design. Data collecting used the questioner and observation sheets. A whole population were samples of this study. They were 35 officer consist of 12 P2TB officers, 12 laboratory officers and 11 doctors. P2TB officers (91.7%), laboratory officers (16.7%) and doctors (100.0%) had a training history less than twice. Workload perception was high category with 41.7% in P2TB officers, 50,0% in laboratory officers and 63,6% in BP physicians. The perception of incentives of P2TB officers (66.7%), laboratory staff (41.7%) and doctors (54.5%) in sufficient category. Most of P2TB officers (66.7%), laboratory officers (50.0%) and doctors (72.7%) had good knowledge level. Practices case detections were suspect screening (41,7%), contact tracking (33,3%) and counseling (25,0%), sputum examination (25,0%) in low level category. Proportion of poorest suspect screenings is mostly at P2TB officers with good knowledge (50,0%) and sufficient workload category (42,9%). 75,0% laboratory facilities and reporting recording in either category. In the tracking of contacts need to be coordinated with the patient so that when tracking all contact can be checked. This study suggests that health worker and Puskesmas should cooperate with private hospitals in order to find suspect and conduct training.